Capturing Contemporary Japan: Differentiation and Uncertainty - Satsuki Kawano, Glenda S. Roberts, and Susan Orpett Long (University of Hawai'i Press, 2014)
This book was conceived in a dark restaurant/bar on one late autumn evening in New Orleans in 2010, during the 109th American Anthropological Association (AAA) annual meeting. After a long day of attending panels, seeing colleagues, and inspecting new books, we needed to enjoy the music for which the city is known—jazz. The result was not a release from work, however. We competed with the drums and discussed what books we were using in our Japan anthropology courses. We agreed that students love narrative-driven books, yet a monograph usually focuses on a few key topics. We wanted a book that was engaging, readable, and rich in ethnographic details that covered many key topics, and it would be even better if the book consisted of never-before-published chapters. We concluded that we should create such a volume. This is the result. This project would not have been possible without the strong support and enthusiasm of the volume’s contributors—all anthropologists who study Japan but work in different parts of the world. We are fortunate to have these colleagues. We would like to express our sincere gratitude to them for sharing their passion for studying Japan and anthropology with our readers. Earlier versions of some of the chapters were presented at the American Anthropological Association annual meeting in Montreal in 2011 and at the Association for Asian Studies annual meeting in Toronto in 2012. We would like to thank everyone who took part in the panels, attended our sessions, and provided useful comments on the presentations. We would like to express our gratitude to Dr. L. Keith Brown, who contributed to our AAA panel but who unfortunately was unable to take part in the book project. We are particularly grateful to Professor Annette Schad-Seifert of Heinrich-Heine-Universität in Duesseldorf for her insightful comments and helpful suggestions. We also appreciated the thoughtful questions raised by Dr. William Kelly during our panel presentations.